Mastering The Old Testament ; v. 20 - Ogilvie, Lloyd J. (Dallas, TX Word, 1990)
Contents : v. 20 : Hosea, Joel, Amos, Obadiah, Jonah
Keywords: Bible O.T. Hosea -- commentaries; Bible O.T. Joel -- commentaries; Bible O.T. Amos -- commentaries; Bible O.T. Obadiah -- commentaries; Bible O.T. Jonah -- commentaries